Phenotypical analysis of Chloramphenicol toxicity in Drosophila - Aditya Satya Pratama; Aizia Risty Rizal; Nurhidayah Ramly; Gimas Fatir Bijaksana; Jihan Atiqah Permatasari; Muhammad Akbar Bahar; Nadila Pratiwi Latada; Mukarram Mudjahid; Risfah Yulianty; Nur Inda Yanti; Firzan Nainu (International Journal of Biomedical Science and Travel Medicine, 2025)
Background: Chloramphenicol is a broad-spectrum antibiotic with serious side effects, including aplastic anemia and gray baby syndrome. While Drosophila melanogaster is a cost-effective and genetically relevant model for toxicological studies, its response to chloramphenicol remains unexamined. This study explores the toxic effects of chloramphenicol in Drosophila to provide insights into its broader biological impact. Methods: This study aims to analyze the toxicity of chloramphenicol in terms of developmental toxicity, locomotor activity, morphology and gene expression status (sod1, sod2, tom40, and indy) in Drosophila melanogaster. The study was conducted on Oregon-R strain D. melanogaster larvae fed with chloramphenicol at concentrations of 625; 1,875; 3,125; and 4,375 ppm. Results: Developmental toxicity assay revealed that chloramphenicol exposure significantly delayed developmental progression, as evidenced by a prolonged transition from larval to pupal stages at concentrations of 3,125 and 4,375 ppm. However, no significant alterations were observed in locomotor activity or morphological characteristics. Moreover, chloramphenicol exposure in D. melanogaster appeared to exert toxic effects by significantly altering the expression of sod1, sod2, and tom40, while having no detectable impact on indy gene expression. Conclusion: High concentrations of chloramphenicol significantly impair larval development in D. melanogaster and alter gene expression profiles. However, adult flies exhibit no observable morphological or locomotor abnormalities compared to controls. These findings highlight that Drosophila larvae are susceptible to chloramphenicol toxicity, making it an ideal phase for assessing the detrimental effects of chloramphenicol.